Association of CCR5Δ32 Deletion and Human Cytomegalovirus Infection With Colorectal Cancer in Tunisia - Chelbi, Hanen; Jelassi, Refka; Belfkih, Sarra; Ben Amor, Amor; Saidi, Nasreddine; Ben Salah, Hamza; Mzoughi, Nabiha; Ben Dhifallah, Imen; Boujelben, Nadia; Ammi, Radhia; Bouratbine, Aida; Zidi, Ines; et al. (Frontiers in Genetics, 2021)
Background and objectives: Human cytomegalovirus (HCMV) and genetic polymorphisms of the chemokine receptor 5 have been suggested as factorsas factors associated with the progression of colorectal cancer (CRC). The aim of the study was to evaluate the associations of both CCR5Δ32 genetic deletion and/or HCMV virus infection with CRC in Tunisia. Materials and methods: The association between HCMV and CRC was validated by Nested PCR technology performed for HCMV and HCMV-specific serum IgG and IgM antibodies were investigated by enzyme-linked immunosorbent assay. Experiments were carried out on 40 tumor and 35 peri-tumor tissues, 100 blood from CRC patients and on 140 blood samples from healthy subjects and finaly serum samples of 80 patients with CRC and 100 healthy individuals. For Aa conventional PCR has been optimized for the detection of CCR5Δ32 in100 CRC patients and 100 healthy subjects. Results: Our results show that HCMV is significantly active in 93% of patients compared to 60% in controls (P <0.0001, OR= 8.85, 95% CI: 3.82 -20.50). Compared to the healthy controls, the titers of IgG and IgM antiCMV antibodies in CRC patients were significantly higher than in healthy subjects (P value<0,0001 for IgG and IgM) . Statistical analysis revealed a lack of association between CCR5Δ32 mutation and colorectal cancer (p=0.788, OR=1.265, 95% CI: 0.228-7.011). Conclusion: our data confirmed that the HCMV infection was related to the development of CRC and that CRC cells may be infected more favorably by HCMV. .Given the importance of the CCR5 in inflammation and therefore CRC progression, further studies still needed to evaluate CCR5 role as a potential candidate gene for CRC susceptibility under other polymorphisms.